"I teach it because it is the biggest threat to health": Integrating sustainable healthcare into health professions education. (4th March 2021) - Brand, Gabrielle; Collins, Jorja; Bedi, Gitanjali; Bonnamy, James; Barbour, Liza; Ilangakoon, Chanika; Wotherspoon, Rosie; Simmons, Margaret; Kim, Misol; Schwerdtle, Patricia Nayna
Abstract: Background: Steering planetary and human health towards a more sustainable future demands educated and prepared health professionals. Aim: This research aimed: to explore health professions educators' sustainable healthcare education (SHE) knowledge, attitudes, self-efficacy and teaching practices across 13 health professions courses in one Australian university. Methods: Utilising a sequential mixed-methods design: Phase one (understanding) involved an online survey to ascertain educators' SHE knowledge, attitudes, self-efficacy and teaching practices to inform phase two (solution generation), 'Teach Green' Hackathon. Survey data was descriptively analysed and a gap analysis performed to promote generation of solutions during phase two. Results from the hackathon were thematically analysed to produce five recommendations. Results: Regarding SHE, survey data across 13 health professions disciplines ( n = 163) identified strong content knowledge (90.8%); however, only (36.9%) reported confidence to 'explain' and (44.2%) to 'inspire' students. Two thirds of participants (67.5%) reported not knowing how best to teach SHE. Hackathon data revealed three main influencing factors: regulatory, policy and socio-cultural drivers. Conclusions: The five actionable recommendations to strengthen interdisciplinary capacity to integrate SHE include: inspire multi-level leadership and collaboration; privilege student voice; develop a SHE curriculum and resources repository; and integrate SHE into course accreditation standards.